Managing coastal resources in the 21st century. Issue 1 (1st February 2007) - Weinstein, Michael P.; Baird, Ronald C.; Conover, David O.; Gross, Matthias; Keulartz, Jozef; Loomis, David K.; Naveh, Zev; Peterson, Susan B.; Reed, Denise J.; Roe, Emery; Swanson, R Lawrence; Swart, Jacques AA; et al.
Abstract : Coastal ecosystems are increasingly dominated by humans. Consequently, the human dimensions of sustainability science have become an integral part of emerging coastal governance and management practices. But if we are to avoid the harsh lessons of land management, coastal decision makers must recognize that humans are one of the more coastally dependent species in the biosphere. Management responses must therefore confront both the temporal urgency and the very real compromises and sacrifices that will be necessary to achieve a sustainable coastal ecosystem, one that is economically feasible, socially just, and ecologically sound.